2008
DOI: 10.1586/17474124.2.5.673
|View full text |Cite
|
Sign up to set email alerts
|

New treatment options for advanced pancreatic cancer

Abstract: Pancreatic cancer has a very high mortality rate and affects approximately 230,000 individuals worldwide. Gemcitabine has become established as the standard therapy for advanced pancreatic cancer; however, the survival advantage is small. Adjuvant chemotherapy using either 5-fluorouracil or gemcitabine is now established in pancreatic cancer as an alternative therapy. Combinations of gemcitabine with either platin agents or capecitabine may be advantageous. Anti-EGFR and anti-VEGF agents have been unsuccessful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 116 publications
0
20
0
Order By: Relevance
“…It is a new generation drug guided on the basis of the antigen/antibody affinity. It is a humanized monoclonal antibody used for blocking vascular endothelial growth factor A and is regarded as an angiogenesis inhibitor [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is a new generation drug guided on the basis of the antigen/antibody affinity. It is a humanized monoclonal antibody used for blocking vascular endothelial growth factor A and is regarded as an angiogenesis inhibitor [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Akt, a major downstream target of PI3K, was originally reported as the cellular counterpart of the viral oncogene, which was amplified in gastric adenocarcinoma [14] . Overexpression of Akt isoforms has now been reported in ovarian, breast, prostate, and pancreatic cancers [16,[33][34][35] . In addition, Akt activity is increased in cancers where the PTEN tumor suppressor is mutated [36] .…”
Section: Discussionmentioning
confidence: 99%
“…84 Currently, the standard of care for advanced pancreatic cancer is the chemotherapeutic drug gemcitabine. 85 Clinical trials of allogeneic vaccines for pancreatic cancer are currently underway and the early phase of trials have reported promising results. Two allogeneic vaccines in currently tested in clinical trials for the treatment of pancreatic cancer include NewLink Genetic's HyperAcute® pancreatic cancer vaccine (Algenpantucel-L) and BioSante Pharmaceutical's GVAX Pancreas Vaccine.…”
Section: Pancreatic Cancermentioning
confidence: 99%